2022
DOI: 10.3389/fimmu.2022.870780
|View full text |Cite
|
Sign up to set email alerts
|

MSC-ACE2 Ameliorates Streptococcus uberis-Induced Inflammatory Injury in Mammary Epithelial Cells by Upregulating the IL-10/STAT3/SOCS3 Pathway

Abstract: In the dairy industry, Streptococcus uberis (S. uberis) is one of the most important pathogenic bacteria associated with mastitis in milk-producing cows, causing vast economic loss. To date, the only real effective method of treating and preventing streptococcal mastitis is antimicrobial therapy. In many inflammatory diseases, mesenchymal stem cells (MSCs) and angiotensin-converting enzyme 2 (ACE2) play an anti-inflammatory and anti-injurious role. Accordingly, we hypothesized that MSCs overexpressing ACE2 (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The differentially expressed genes (| log2 (fold change) | >1.5) involved in cytokinecytokine receptor interactions were analyzed using qRT-PCR (Figure S5E) showed the most statistically significant up-regulation of IL-10RA expression in CAV1-knockdown and circGNB1-knockdown HCs (Figure 8B and Figure S5E). Given that many studies have shown that the IL-10 signalling pathway is one of the most essential antiinflammatory signalling pathways, [31][32][33] we speculated that the circGNB1/miR-152-3p/RNF219/CAV1 axis may mediate OA progression through the IL-10 pathway. Using flow cytometric analysis, we found that down-regulation of circGNB1, RNF219, and CAV1 and up-regulation of miR-152-3p significantly up-regulated IL-10R expression in HCs (Figure 8C).…”
Section: 9mentioning
confidence: 99%
“…The differentially expressed genes (| log2 (fold change) | >1.5) involved in cytokinecytokine receptor interactions were analyzed using qRT-PCR (Figure S5E) showed the most statistically significant up-regulation of IL-10RA expression in CAV1-knockdown and circGNB1-knockdown HCs (Figure 8B and Figure S5E). Given that many studies have shown that the IL-10 signalling pathway is one of the most essential antiinflammatory signalling pathways, [31][32][33] we speculated that the circGNB1/miR-152-3p/RNF219/CAV1 axis may mediate OA progression through the IL-10 pathway. Using flow cytometric analysis, we found that down-regulation of circGNB1, RNF219, and CAV1 and up-regulation of miR-152-3p significantly up-regulated IL-10R expression in HCs (Figure 8C).…”
Section: 9mentioning
confidence: 99%
“…In neuronal injury and NDs, IL-10 can inhibit microglial activation, reduce the production of inflammatory cytokines, and thereby decrease neuronal pyroptosis and damage (Heinzerling et al, 2020). IL-10 can also regulate cytokine signaling pathways, such as inhibiting NF-κB and MAPK activities, further reducing the inflammatory response and neuronal pyroptosis (Yan et al, 2022). IL-4 and IL-13 are two anti-inflammatory cytokines with similar functions that mainly regulate microglial polarization, inducing microglia to transform into the M2 phenotype (Fu et al, 2022).…”
Section: Replacement Of Activated Microglia Alleviates Neuronal Pyrop...mentioning
confidence: 99%